Recent advances in functionalized micro and mesoporous carbon materials: synthesis and applications. (26th March 2018) - Benzigar, Mercy R.; Talapaneni, Siddulu Naidu; Joseph, Stalin; Ramadass, Kavitha; Singh, Gurwinder; Scaranto, Jessica; Ravon, Ugo; Al-Bahily, Khalid; Vinu, Ajayan
Abstract : This review provides the recent progress and advances in the design, synthesis and high throughput applications of functionalized micro and mesoporous carbon materials. Abstract : Functionalized nanoporous carbon materials have attracted the colossal interest of the materials science fraternity owing to their intriguing physical and chemical properties including a well-ordered porous structure, exemplary high specific surface areas, electronic and ionic conductivity, excellent accessibility to active sites, and enhanced mass transport and diffusion. These properties make them a special and unique choice for various applications in divergent fields such as energy storage batteries, supercapacitors, energy conversion fuel cells, adsorption/separation of bulky molecules, heterogeneous catalysts, catalyst supports, photocatalysis, carbon capture, gas storage, biomolecule detection, vapour sensing and drug delivery. Because of the anisotropic and synergistic effects arising from the heteroatom doping at the nanoscale, these novel materials show high potential especially in electrochemical applications such as batteries, supercapacitors and electrocatalysts for fuel cell applications and water electrolysis. In order to gain the optimal benefit, it is necessary to implement tailor made functionalities in the porous carbon surfaces as well as in the carbon skeleton through the comprehensive experimentation. These most appealing nanoporous carbon materials can be synthesized through the carbonization of high carbon containing molecular precursors by using soft or hard templating or non-templating pathways. This review encompasses the approaches and the wide range of methodologies that have been employed over the last five years in the preparation and functionalisation of nanoporous carbon materials via incorporation of metals, non-metal heteroatoms, multiple heteroatoms, and various surface functional groups that mostly dictate their place in a wide range of practical applications.